Generational categories: a broken basis for human resource management research and practice - Parry, Emma; Urwin, Peter (Wiley, 2021)
This provocation challenges the use of generational categories as a valid and useful basis for development of human resource management (HRM) research and practice. We present two provocations. First, that a focus solely on year of birth as a driver of attitudes, values and behaviours is wholly inadequate. Second, we go beyond existing empirical challenges to argue that any approach to the study of generations that focuses solely on generational categories should be abandoned. We consider the theoretical basis for generations, together with specific examples from empirical studies to show how the current reliance on largely unsubstantiated categories leaves even longitudinal studies unable to make an effective contribution to this field. We draw on cross-disciplinary insights to consider the implications for academic research and for HRM practice, showing how the current approach limits the usefulness of findings and suggesting a potential way forward.
Keywords: Validity; Context; Millennials; Generations